Dento-Skeletal dimensions in individual with skeletal CL I and variations in the lower anterior facial height (Mustansiria Dental Journal, 2018)
Aims of the study: This study is designed to evaluate some of the dental and skeletaldimensions of individuals with normal and excessive lower anterior facial heightand to establish the effect of these two groups (normal and excessive lower anteriorfacial height) on dento-facial structures for Iraqi adult sample at 18-25 years of agewith skeletal and dental CL I occlusion.Material and Method: The sample consisted of (80) previously taken lateralcephalometric radiographs (40 males and 40 females).The sample was divided intotwo groups (normal lower anterior facial height group and excessive lower anteriorfacial height group) each of them composed of 40 subjects (20 males and 20 females)Results: The results showed that all linear measurements were significantly larger inmales than females in two groups. No significant differences in most of dentoskeletaldimensions were found between the two groups. Highly significantdifferences for lower anterior dental height (LADH) and upper posterior dentalheight (UPDH) were found between the two groups.Conclusion: Four anatomical parts were responsible for the variation of the loweranterior facial height upper anterior dental height (UADH) , lower anterior dentalheight (LADH) , upper posterior dental height (UPDH) and the inclination of themandibular plane in relation to the anterior cranial base (SN-MP angle).